Synthesis and characterization of polyaniline/ graphene composite nanofiber and its application as an electrochemical DNA biosensor for the detection of mycobacterium tuberculosis - Mohamad, Fatimah Syahidah; Zaid, Mohd Hazani Mat; Abdullah, Jaafar; Zawawi, Ruzniza Mohd; Hong, Ngee Lim; Sulaiman, Yusran; Rahman, Norizah Abdul (Multidisciplinary Digital Publishing Institute, 2017)
This article describes chemically modified polyaniline and graphene (PANI/GP) composite nanofibers prepared by self-assembly process using oxidative polymerization of aniline monomer and graphene in the presence of a solution containing poly(methyl vinyl ether-alt-maleic acid) (PMVEA). Characterization of the composite nanofibers was carried out by Fourier transform infrared (FTIR) and Raman spectroscopy, transmission electron microscopy (TEM) and scanning electron microscopy (SEM). SEM images revealed the size of the PANI nanofibers ranged from 90 to 360 nm in diameter and was greatly influenced by the proportion of PMVEA and graphene. The composite nanofibers with an immobilized DNA probe were used for the detection of Mycobacterium tuberculosis by using an electrochemical technique. A photochemical indicator, methylene blue (MB) was used to monitor the hybridization of target DNA by using differential pulse voltammetry (DPV) method. The detection range of DNA biosensor was obtained from of 10−6–10−9 M with the detection limit of 7.853 × 10−7 M under optimum conditions. The results show that the composite nanofibers have a great potential in a range of applications for DNA sensors.